Leaf Area Estimation in Yam Bean ( Pachyrrhizus erosus L.) using Linear Measurement of Leaf Parameters - Suresh Kumar, J; More, Sanket J; Ravi, V; Byju, G; George, James (JOURNAL OF ROOT CROPS, 2017)
Yam bean is a leguminous minor tuber crop grown in tropical regions for its turnip like edible tuberous roots for its delicacy. The seeds are protein rich and have insecticidal properties. So far, there is no information available in this crop for the estimation of leaf area; hence a simple method for leaf area estimation in yam bean ( Pachyrrhizus erosus L.) was developed. In yam bean each leaf had three leaflets. Measurements on the length, breadth of leaflets of varying size were recorded. There was significant positive correlation between length (L) and area (A) (r = 0.889) and; breadth (B) and area (A) (r = 0.927) of leaflet. The factor (F) of relationship between L and A of leaf was 6.129 and that between B and A of leaflet was 5.569. The relation between product of length and breadth (P) and A of leaflet was also significant (r = 0.749) and the F between P and A was 0.643. The linear regression equation between L and A, B and A and between P and A were Y = 10.99x . 40.88, Y = 7.147x . 14.58 and Y = 0.571x + 5.702 respectively. The coefficient of determination (r 2 ) values between L and A, B and A; and P and A were 0.792, 0.860 and 0.933 respectively. The r 2 value observed between P and A near to 1 (0.933) suggested that the regression equation was good fit. Therefore, using the F value derived from P, the total leaf area of a plant can be calculated by the formula: Total leaf area = P of a single leaflet (average value of few observations) x 0.64 x 3 x total number of leaves per plant. The coefficient of determination between dry weight of leaflet to area was closer to 1 (r 2 = 0.903) and significant positive correlation coefficient value (r = 0.950) between weight of dry leaflet and area suggest that the dry leaf weight method can also be used for calculating leaf area of yam bean. The factor (F) derived between weight of dry leaflet and area of leaflet was 0.233. From the F value, the total area of yam bean can be calculated by the formula: Total leaf area = weight of a single dry leaflet (average of few leaflets) x 0.233 x 3 x total number of leaves per plant.